PENGARUH PENCAMPURAN DAN RASIO PREKURSOR/DOPAN DALAM PEMBUATAN LAPISAN TIPIS FLUORINE DOPED TIN OXIDE (FTO) BERBASIS TIMAH (II) KLORIDA[The Effect of Mixing Condition and Dopant/Precursor Ratio in Fabrication of Fluorine Doped Tin Oxide (FTO) Thin Film Based on Tin (II) Chloride] - Lalasari, Latifa Hanum (Jurnal Metalurgi, 2015)
Fluorine-doped tin oxide (FTO) is an oxide that is commonly used in the coating on the glass treated a particular treatment in order to be able to conduct electricity. FTO is expected to replace indium tin oxide (ITO) whose raw materials are very expensive and available in limited quantities. Preliminary experiments on the manufacture of F-SnO2 thin film done with using combinations of sol gel method and dip coating. This experiment used the raw material of tin (II) chloride hydrate (SnCl2.2H2O) as precursors and ammonium fluoride (NH4F) as doping. The results showed that the processing time between the mixing of precursors and doping was not so affect the stability of the solution. The significant factor affecting was the concentration ratio of the dopant/precursor and the conditions of mixing between the precursors and doping. The concentration ratio of the dopant/precursors of 10% produced the most stable conductive solution (US-1-½-½) with a thin layer of FTO has generated more regular hexagonal morphology, uniform and phase of Sn4OF6.